Canopy characteristics and tillering dynamics of Marandu palisade grass pastures in the rainy-dry transition season - Santana, S. S. [UNESP]; Brito, L. F. [UNESP]; Azenha, M. V. [UNESP]; Oliveira, A. A. [UNESP]; Malheiros, E. B. [UNESP]; Ruggieri, A. C. [UNESP]; Reis, R. A. [UNESP] (Wiley-Blackwell, 2017)
The objective of this study was to evaluate the effect of pasture management during the rainy-dry transition season in Jaboticabal, Brazil, on the structural and tillering characteristics of Marandu palisade grass. The treatments were as follows: 15 cm sward height in the rainy season and ungrazed in the rainy-dry transition season (15/0); 25 cm sward height during the rainy season and fixed stocking rate of 2 . 5 AU ha(-1) during the rainy-dry transition season (25/2.5); and 35 cm sward height in the rainy season and fixed stocking rate of 2 . 5 AU ha(-1) in the rainy-dry transition season (35/2.5). There were more herbage mass, stem and dead herbage mass in treatments 25/2.5 and 35/2.5 than 15/0. Tiller appearance rate was greater in treatment 15/0 and tiller mortality rate was higher in treatment 35/2.5 compared to treatment 15/0. Tiller population stability index was 1 in treatment 15/0 and lower in treatment 35/2.5. Although treatment 15/0 showed favourable structural and tillering characteristics, it also has the lowest herbage mass. Treatment 25/2.5 can be regarded as an adequate management strategy for Marandu palisade grass, since it has similar herbage mass and better tillering characteristics than treatment 35/2.5.
Keywords: Brachiaria brizantha; ecophysiology; pasture structure; tiller